A pilot randomized controlled trial comparing effectiveness of prism glasses, visual search training and standard care in hemianopia - Rowe, Fiona; Conroy, Elizabeth J.; Bedson, Emma J.; Cwiklinski, Emma; Drummond, Avril E.R.; Garcia-Finana, Marta; Howard, Claire; Pollock, Alex; Shipman, Tracey; Dodridge, Caroline; Macintosh, Claire; Johnson, Stevie; et al. (Wiley, 2017)
Objective: Pilot trial comparing prism therapy and visual search training, for homonymous hemianopia, to standard care (information only). Methods: Prospective, multicentre, parallel, single-blind, three-arm RCT across fifteen UK acute stroke units. Participants: Stroke survivors with homonymous hemianopia. Interventions: Arm a (Fresnel prisms) for minimum 2 hours, 5 days/week over 6- weeks. Arm b (visual search training) for minimum 30 minutes, 5 days/week over 6-weeks. Arm c (standard care-information only).Inclusion criteria: Adult stroke survivors (>18 years), stable hemianopia, visual acuity better than 0.5logMAR, refractive error within 5Dioptres, ability to read/understand English, and provide consent. Outcomes: Primary outcomes were change in visual field area from baseline to 26 weeks and calculation of sample size for a definitive trial. Secondary measures included Rivermead Mobility Index, Visual Function Questionnaire 25/10, Nottingham Extended Activities of Daily Living, Euro Qual, Short Form-12 questionnaires and Radner reading ability. Measures were post-randomisation at baseline and 6, 12, 26 weeks. Randomisation: Randomisation block lists stratified by site and partial/complete hemianopia. Blinding: Allocations disclosed to patients. Primary outcome assessor blind to treatment allocation. Results: 87 patients were recruited: 27 - Fresnel prisms, 30 – visual search training and 30 - standard care. 69% male; mean age 69 years (SD 12). At 26 weeks, full results for 24, 24 and 22 patients respectively were compared to baseline. Sample size calculation for a definitive trial determined as 269 participants per arm for a 200 degree2 visual field area change at 90% power. Non-significant relative change in area of visual field was 5%, 8% and 3.5% respectively for the three groups. Visual Function Questionnaire responses improved significantly from baseline to 26 weeks with visual search training (60 (SD19) to 68.4 (SD20)) Compared to Fresnel prisms (68.5 (SD16.4) to 68.2 (18.4): 7% difference) and standard care (63.7 (SD19.4) to 59.8 (SD22.7): 10% difference), p=0.05. Related adverse events were common with Fresnel prisms (69.2%; typically headaches). Conclusions: No significant change occurred for area of visual field area across arms over follow-up. Visual search training had significant improvement in vision-related quality of life. Prism therapy produced adverse events in 69%. Visual search training results warrant further investigation.